Psychological morbidity in soldiers after spinal cord injury - Madhusudan, T. (Ind Psychiatry J, 2019)
BACKGROUND: Spinal cord injury (SCI) patients usually experience multiple and ongoing, neurological, and other medical problems with significant damage to the social and psychological well-being of themselves and their families. MATERIALS AND METHODS: Soldiers with SCI transferred to the regional centre after suitable stabilization of their fractures and general physical condition were included in the study. The baseline assessment included a diagnostic interview and review of case notes for a comprehensive, multi-axial diagnosis. The participants were assessed using the Barthel’s Index, the Hospital Anxiety and Depression Scale, the General Health Questionnaire, Quality of life (QOL) Index, AFMC stressful life event Scale, and the Social Support Survey with the current defense or coping style also being recorded. Similar assessments were repeated at 1 month, 6 months, and at 1 year after intake. RESULTS: It was noticed that the mean scores on the Hospital Anxiety and Depression Scale were below the cut-off point for diagnosable disorder, or in the mild end of the spectrum. However, the measures of psychological distress and QOL showed significantly high mean scores. Anxiety Scores showed little variation over time initially, and none of the mean differences (t values) reached statistical significance. However, when the scores of intake and those at 6 months are compared, there was a statistically significant improvement. Depression scores, on the other hand, showed a steady improvement with each assessment. General lack of well-being and psychological distress along with poor QOL remained high throughout the period of assessment with little variation over time .These morbidity measures could not be accounted for by variations in stressful life-event scores or by variations in degree of disability. Although the negative correlation between anxiety and depression scores and those on the QOL index approached conventional levels of significance, there was little correlation overall between morbidity measures and the putative modifying variables at any stage of assessment. CONCLUSIONS: Although psychological symptoms of depressive and anxious spectrum was virtually universal, psychiatric illness at syndromal intensity warranting a formal psychiatric referral and management was rare in patients with SCI in the 1(st) year. The general well-being and QOL were expectedly dismal throughout. Expected correlations between the measures of social support and degree of disability with the measures of anxiety, depression, subjective distress, and QOL were not demonstrated .There is a need to look beyond these and explore factors such as lack of information, physical morbidity, quality of social support, and dependence for the activities of daily living to evolve a nuanced approach toward the challenge that these clientele represent.